Investigating Phrase Usage Errors in the English Language Education Study Program: A Student-Centered Analysis - Magvirah Octasary; Rahmatul Ummu Arifin; Desrin Lebagi (FKIP Universitas Khairun, 2025)
The primary objectives of this study were (1) to identify the types of errors made by third-semester students in the use of noun phrases and (2) to determine the most frequently occurring error type. To achieve these objectives, a descriptive qualitative research design was employed. Data were collected using two types of assessments: multiple-choice questions and essay writing tasks. These instruments were designed to elicit various forms of noun phrase usage to allow for a comprehensive analysis of student performance. Based on the data analysis, four main types of grammatical errors were identified (1) omission, addition, misformation, and misordering. Among these, misformation errors were found to be the most prevalent. This suggests that while students may understand the general structure of noun phrases, they struggle with selecting the correct grammatical forms, such as appropriate determiners, pluralization, or adjective-noun order. The high frequency of misformation errors may stem from several interrelated factors, including interference from the students' first language, insufficient grammatical instruction, and limited exposure to authentic English usage